Livelihood analysis of lentil (Lens culinaris) farmers in Chanduali district of Uttar Pradesh - DOGRA, ATUL; SARKER, ASHUTOSH; SAH, POOJA; HASSAN, ADEN AW (The Indian Journal of Agricultural Sciences, 2016)
Lentil (Lens culinaris Medik.) is one of the most important pulse crops in India, which plays a major role in supplementing the income of small and marginal farmers of Chanduali district of Uttar Pradesh. One of the major constraints of pulses in India and also in lentil is low productivity due to non-adoption of recommended package and practices and improved varieties. In India, lentil is grown about 1.42 million hectare of land with production of 1.13 million tonnes in 2012-13. But yield of Indian lentils (797 kg/ha) is far below the world average (1 139 kg/ha) which require strong research as well as extension. The results of improved technological intervention brought out that the yield of lentil could be increased by 28.56% to 49.24%, if proper package and practices are followed.